Constitutional Government in the United States - WILSON, Woodrow (Colombia University Press, 1908)
Wilson's classic study and re-thinking of government in states and federal organizations such as Congress, the courts, executive agencies, and the presidency -- just a few years before he gained that office. While President of Princeton and a professor in political science, Wilson revisited some of his theories from prior books and delivered this life's work on the subject. It is still read and considered thoughtfully by history buffs, political science students, and constitutional lawyers. American history is punctuated with treatises that mark a shift in political thought and influence the role of government. These treatises, influential both in their day as well as to modern scholarship, are central to an understanding of the development of modern political behavior. 'Constitutional Government in the United States' is certainly one such treatise. Written as a series of lectures just over a century ago, this book proposed a dramatic shift in the American perception of the role of the Constitution, as well as presenting a thoughtful exposition on the three branches of United States government. Wilson endorsed the theory that the Constitution is evolutional, Darwinian even -- and his organic theory is still fervently debated among jurists, economists, and political theorists. All Legal Legends Series contributions from Quid Pro Books feature new introductions with historical context, modern formatting, and hyper-accurate care in rendering the author's text, unlike most such republications today. Another unique feature: page numbers from the original 1908 text are inserted into the text, allowing continuity of referencing and syllabi. This even allows the included and extensive subject-matter Index, from the original book, to make sense and have practical value to the modern reader